Clinical and histopathological analysis of the patients undergoing appendectomy - Koirala, Kamal; KC, Shiva Raj; Simkhada, Ganesh; Mukhiya, Rupesh; Pokharel, Nisheem; KC, Geetika (Journal of Pathology of Nepal, 2018)
Background: Acute appendicitis is one of the most common surgical emergencies, but the diagnosis is difficult even with the sophisticated diagnostic tools. The aim of this study is to analyze the clinical and histopathological features of acute appendicitis and to see how reliable the clinical scoring system modified Alvarado score in our setup. Materials and Methods: This was a retrospective observational study of patients who underwent appendectomy at KIST Medical College and Teaching Hospital during two years. The clinical characteristics of the patients in terms of modified Alvarado scoring were outlined. The diagnosis of acute appendicitis was confirmed by histopathological examination. The data were tabulated in MS-Excel and statistically analyzed using SPSS statistics software, version 21. Results: Among 118 patients, who underwent appendectomy, 69 were male and 49 were female with male to female ratio of 1.41:1 and mean age of 27.46±12.724 years.The clinical diagnosis of acute appendicitis was more likely (MAS 7-9) in 56 patients, less likely (4–6) in 44 patients and unlikely (MAS 1-3) in 18 patients. The highest incidence of acute appendicitis was observed in 19-40 years and the lowest incidence in 61 years or above. After histopathological examination, 52 patients out of 56 in the more likely group had acute appendicitis and 4 patients had non-inflamed appendices. 7 patients out of 62 in the less likely and unlikely groups had acute appendicitis and 55 patients had non-inflamed appendices. The overall negative appendectomy rate was 9.32 percent. Conclusion: Our clinical practice of using modified Alvarado score in the diagnosis of acute appendicitis is effective, easy and non-invasive.